Intrathecal chemotherapy for the management of lymphoblastic lymphoma in a 4-year-old dog: a case report - Lyseight, Filipa Louise Simões; Dupont, Christophe Osterreicher Cunha; Cherubini, Giunio Bruto (Frontiers in Veterinary Science, 2023)
Intrathecal chemotherapy is used in human medicine for the treatment or prophylaxis of CNS hematopoietic neoplasia. However, the clinical benefits in veterinary medicine have been scarcely documented. A 4-year-old male entire cross-breed dog presented with a 24-h history of severe lethargy, pelvic limb weakness, and urinary retention. Examination revealed generalized peripheral lymphadenomegaly, and the neurological findings were suggestive of a myelopathy in the region of T3-L3. Following the diagnosis of multicentric lymphoblastic B-cell lymphoma (stage Vb), a modified L-LOP with cytosine arabinoside was started, and complete clinical remission was achieved. After 4 weeks, there was acute neurological deterioration (spinal pain and proprioceptive deficits) without peripheral lymphadenomegaly. MRI findings and CSF analysis were consistent with meningeal and spinal cord lymphoma infiltration at the level of L3. Intrathecal chemotherapy (cytosine arabinoside and methotrexate) were administered in the cisterna magna with systemic dexamethasone and analgesia. Clinical signs were resolved within 24 h, and the patient remained asymptomatic for 3.5 weeks. After this period, CNS relapse (proprioceptive deficits and severe thoracolumbar pain) was suspected, and repeat intrathecal chemotherapy was declined. The patient was humanely euthanized 9 weeks after the initial diagnosis. This is the first report on the clinical benefit of intrathecal chemotherapy with a combination of methotrexate and cytarabine for the management of CNS lymphoma in dogs. Based on our case, intrathecal chemotherapy with methotrexate and cytarabine can induce a short-lasting CNS clinical remission (3 weeks).